Collaborative Governance Model in Empowering Mountain Communities through Strengthening English Education and Religious Values: The Implementation of INASS Thematic Community Service Program (KKN) in Tombolo Pao District - Suryani Jihad (Indonesian Journal Publisher, 2025)
The Thematic Community Service Program (KKN) of Institut ‘Aisyiyah Sulawesi Selatan (INASS) in Tombolo Pao District represents the implementation of the university’s Tri Dharma of Higher Education in empowering mountain communities through a collaborative and participatory governance approach. The region boasts significant potential in horticulture, featuring strawberries, passion fruit, and other locally produced agricultural products, as well as strong religious and cultural values. However, the community still faces limited educational access, low social literacy, and insufficient English language competence. This study aims to develop a model of collaborative governance involving students, village governments, and local communities to strengthen their social, economic, and educational capacities. The program was implemented over one month, from October 13 to November 12, 2025, involving 40 students from various study programs, divided into six multidisciplinary groups (six to seven students each) and guided by six field supervisors. Data were collected through field observation and in-depth interviews with 20 village officials, 50 community members, 40 INASS students, and 6 field supervisors. The data were analyzed both descriptively and qualitatively, using a theoretical framework that incorporates social collaboration and community empowerment. The results show an increase in community participation in social activities, stronger religious engagement, and the advancement of community-based education, particularly in English language teaching facilitated by INASS students. The implementation of a collaborative governance model effectively enhanced inter-actor communication, strengthened social networks, and promoted the sustainability of community empowerment initiatives based on religious values and English literacy.